(untitled) - Joyce Stith (Boston, Massachusetts, 1982)
This book is designed for the basic writing course that covers all skills required for and all aspects of beginning essay writing. Starting with essay organization including thesis, outline, body paragraphs, introduction, and conclusion, the text then covers identification of subjects, verbs, and clauses and correction of run-together sentences and fragments
Keywords: english language - rhetoric,english language - writing